2006
DOI: 10.3143/geriatrics.43.207
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and psychological symptoms, cognitive impairment and caregiver burden related to Alzheimer's disease patients treated in an outpatient memory clinic

Abstract: These analyses will contribute to better assessment of AD patients and their caregivers, hopefully resulting in better support for them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In addition, there were no significant differences in neuropsychological cognitive sub-scales of COGNISTAT scores between the two groups. These results confirm the results of previous studies concerning the relations between delusion and neuropsychological cognitive functions (Burns et al, 1990;Ikeda, 2004;Migliorelli et al, 1995;Takechi et al, 2006). Social cognitive functions construct representations of relationships between oneself and others, and cannot be generally assessed by neuropsychological cognitive tests (Adolphs, 2001).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, there were no significant differences in neuropsychological cognitive sub-scales of COGNISTAT scores between the two groups. These results confirm the results of previous studies concerning the relations between delusion and neuropsychological cognitive functions (Burns et al, 1990;Ikeda, 2004;Migliorelli et al, 1995;Takechi et al, 2006). Social cognitive functions construct representations of relationships between oneself and others, and cannot be generally assessed by neuropsychological cognitive tests (Adolphs, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…Ikeda (2004) reported that there were no significant differences in sub-scale scores on the Alzheimer's disease Assessment Scale (ADAS) between AD patients with and without delusion of theft. Takechi et al (2006) reported that there were no significant differences in scores on the word fluency test, category cued memory test and clock drawing test between AD patients with and without delusion of theft, although there was a significant difference in their MMSE scores. Other studies also reported that there was no significant correlation between delusion of theft and cognitive functions (Kazui et al, 2006;Terada et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…While some previous studies on nursing caregivers for dementia patients have investigated elements such as care burden7, 8 ) , depression9, 10 ) and sleep11 ) , we were unable to locate any reports that had investigated whether the nursing caregiver consciously providing only minimal nursing care has a beneficial effect on the ADL/IADL independence of dementia patients.…”
Section: Introductionmentioning
confidence: 91%
“…While some authors found a significant association between BPSD and cognitive function [6,7] , for others, behavioral syndromes and cognitive impairment seemed to be relatively independent dimensions and should be examined individually for different prognostic significance [8][9][10] .…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 99%